Investigating the effect of design parameters on the performance of microfluidics electrochemical biosensor - Basheer, Esmail Abdullah Mohammed (2016)
The development of advanced technology for medical and biological diagnostician is significantly increased. Electrochemical biosensors become more desirable since it offered an attractive replacement for the bulky and expensive analytical instruments. The design and fabrication of a novel electrochemical biosensor using microfluidic chip are the aims of this research. Additionally, the effects of the design parameters including the microchannel size and electrode size are to be investigated. The designed biosensor is consisting of two chips; a microfluidic chip which was made of PMMA (polymethyl methacrylate) where the microchannel is created. The second chip is made of glass, where the three electrodes cell was fabricated. This design offered more flexible testing and multi diagnostician at the same chip. The performance of such biosensor is then examined using the electrokinetic and cyclic voltammetry techniques in order to ensure the quality of the biosensor. The effect of the microchannel size on the performance of the sensor was then investigated by conducting cyclic voltammetry testing for four different sizes of the fabricated channels at electrode size of 1 OO.im. Likewise, similar channels sizes were investigated at 200j. electrode size. The fabricated chips morphology showed the smoothness on the surface in both the microchannel chip and the electrode chip. No defects on the fabricated chips were reported. The electrokinetic properties of the microchannel were found to be affected by the size of both the microchannel and the electrode. The highest sensitivity of the sensor was reported at microchannel size of 700 and electrode size of 200tm. High accuracy and fast responding electrochemical bio sensor are expected to be produced through the optimization of the microchannel size and the electrode surface area.